The determinants of green finance and effect on the banking sector - Yusuf Gör; Bilgehan Tekin (Financial Internet Quarterly, 2023)
This study examines the prerequisites and challenges faced by local and foreign commercial banks in Türkiye in supporting green business initiatives. This study uses backward logistic regression analysis to identify variables affecting green financing practices using annual data from Turkish deposit banks from 2012 to 2021. This study addresses the growing interest in understanding the role of commercial banks in promoting green finance and contributes to the existing literature by revealing the current efforts of Turkish commercial banks in this area. The main findings show that factors influencing green financing practices are derivative financial assets, loans, tangible assets, equity capital, company size, female representation on boards, presence of audit committees and company experience. The study highlights the relationship between these factors and green financing methods adopted by depository banks. It is worth noting that the assets of these banks were built within the framework of green financing and practices such as green buildings, green loans and green bonds were introduced. In addition, the size and experience of custodian banks help influence their green financing practices. The findings provide a framework for policy makers, practitioners and academics who wish to gain a deeper understanding of the dynamics of Turkish financial institutions and green finance.
Keywords: G21; G23; M41; 330; Investment; Green Finance; Profitability; Banking Sector; Logistic Regression; Commercial Banks